(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
This paper describes a reserved-phase HPLC method for detecting frequently-used neonicotinoid insecticides, acetamiprid (ATP) and imidacloprid (ICP), using an isocratic 100 % water mobile phase.Â Chromatographic separations were performed an InertsilÂ® WP300 C4 with water mobile phase and a photodiode-array detector.Â The total run time was < 7 min.Â The system suitability was well within the international acceptance criteria. Â The detection limits were 0.013 Î¼g ml-1 for ATP and 0.015 Î¼g ml-1 for ICP, respectively.Â A harmless HPLC method for simultaneous detecting ATP and ICP was developed and may be further applied to the quantification in foods. Â Â